Triple Jeopardy : Daniel Pitt #2 - Perry, Anne (New York : Ballantine Books, 2019)
"Young lawyer Daniel Pitt must defend a British diplomat who's accused of a theft that may hide a deadly crime in this compelling novel from the New York Times bestselling author of Twenty-one Days. Daniel Pitt, along with his parents, Charlotte and Thomas, is delighted that his sister Jemima has returned to London from the States for a visit. But it's not on the happiest of terms, since a violent theft just before her departure has left Jemima's good friend frightened and missing a treasured family heirloom. The thief appears to be a man named Sydney--a British diplomat stationed in America who, in a cowardly move, has fled to London, claiming diplomatic immunity. But when Daniel is forced to defend Sydney in court, he grows suspicious that he's not getting the whole story; so the lawyer puts on his detective hat to search out what information may be missing. With the help of plucky scientist Miriam Blackwood, Daniel parses through the evidence, and what begins as a stolen necklace turns out to have implications in crimes far greater--including a possible murder"--.
"Young lawyer Daniel Pitt must defend a British diplomat who's accused of a theft that may hide a deadly crime in this compelling novel from the New York Times bestselling author of Twenty-one Days. Daniel Pitt, along with his parents, Charlotte and Thomas, is delighted that his sister Jemima has returned to London from the States for a visit. But it's not on the happiest of terms, since a violent theft just before her departure has left Jemima's good friend frightened and missing a treasured family heirloom. The thief appears to be a man named Sydney--a British diplomat stationed in America who, in a cowardly move, has fled to London, claiming diplomatic immunity. But when Daniel is forced to defend Sydney in court, he grows suspicious that he's not getting the whole story; so the lawyer puts on his detective hat to search out what information may be missing. With the help of plucky scientist Miriam Blackwood, Daniel parses through the evidence, and what begins as a stolen necklace turns out to have implications in crimes far greater--including a possible murder"--
Keywords: Pitt, Charlotte (Fictitious character) -- Fiction; Pitt, Thomas (Fictitious character) -- Fiction; Pitt, Daniel (Fictitious character) -- Fiction; Murder -- Fiction; Police spouses -- Fiction; Police -- England -- London -- Fiction; Private investigators -- England -- London -- Fiction; FICTION / Mystery & Detective / Historical; FICTION / Historical; FICTION / Mystery & Detective / Traditional British